A Case of an Epithelioid Hemangioendothelioma Arising from the Innominate Vein Mimicking Cervical Metastatic Lymphadenopathy. (12th December 2016) - Brill, Jason B.; Schwartz, Isaac E.; Prescher, Lindsey M.; Pratt, Theodore C.
Abstract : Background. Epithelioid hemangioendothelioma (EHE) is a rare tumor usually presenting in soft tissue. EHE is a vascular malignancy of intermediate clinical behavior, with a histologic appearance of endothelial cells growing in nests or cords. Although EHE often originates from a vessel, it is relatively rare for a primary vascular EHE to originate from a large vein or artery. Occurrence in the mediastinum is exceptionally rare. There are no known associations with other malignancies. Case Presentation. We present a case of mediastinal invasive EHE in a 39-year-old female with concurrent papillary thyroid cancer. She initially presented with a thyroid mass found by her primary care provider, with preoperative imaging concerning for extension into the superior mediastinum. Operative exploration revealed a mediastinal mass distinct from her thyroid carcinoma with invasion into the great vessels, requiring off-pump interposition graft bypass for en bloc resection. Final pathology confirmed pT3N1b multifocal papillary thyroid carcinoma with a separate grade 1 pT1b EHE. Review of the literature describes the demographics, updated pathologic outcomes, histologic findings, and reported incidence of EHE. Conclusions. This is the first reported case of thyroid malignancy with separate and concurrent EHE. Surgeons should remain aware of this entity given its variable behavior. Although initially described as an indolent neoplasm, tumors with poor prognostic factors have been shown to be locally aggressive.